Plan de marketing para mejorar la gestión y comercialización de agroindustriales Ordoñez del Cantón Quevedo año 2010-2011 - Ordoñez Rodríguez, Marlon Manuel (2011)
Ordonez is a leading agribusiness company with 14 years experience, managed by Mr. Lauro Ordoñez Conce, dedicated to the production and distribution of agricultural machinery. This marketing plan aimed at Agroindustriales Ordoñez is the purpose of manufacturing products to improve management and marketing from 2011 through situational analysis of the company, determining the internal and external company through a SWOT, up to propose a marketing plan designed for Agribusiness Ordoñez. The research was carried out in Agribusiness Ordoñez played their activities in the city of Quevedo Province Rivers Its facilities are located at Km 2 of the way to Santo Domingo simple sampling was used to determine population size the sample which was used with a confidence level of 96% The standard error of the sample of 449 farmers and 4% as a result gave us a total of 267 surveys. From the results of field research showed that in the market for the marketing of agro-industrial machinery second in market share is Agroindustrial Ordonez. The advertising campaign will have two stages. The first will begin in the months of February March and April 2011 with the purpose of communicating the brand and marketing to users. The second will begin in June in July 2011 and continue throughout the month of agosto/2011. Will be held in two stages: first in February and the second in June. Each stage will last 60 days. In the months of June and July 2011.